PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROJECT BASED LEARNING PADA MATERI MENULIS PUISI SISWA KELAS X SMA - Siti Chairani; Ria Ariesta; Noermanzah Noermanzah (UNIB Press, 2026)
The LKPD used by teachers is not student-centered and has limited worksheets that encourage students to be more creative in writing poetry. As a result, LKPD for project-based learning-based poetic text composing must be developed. Because of this, the goal of this research is to create a project-based learning-based poetry writing worksheet that both instructors and students may utilize with success. The five steps of the ADDIE Research and Development model analysis, design, development, implementation, and evaluation are used in this kind of study. This study's data gathering methods included surveys, trials, and examination of LKPD materials used by instructors. The study's findings demonstrate that project-based learning-based learning activities are the LKPD that educators and students need. The plan created for this study consists of five important components, namely the identity of the LKPD, learning instructions, learning outcomes and objectives, work steps, and assessment. The characteristics of developing this LKPD are at the project based learning stage starting from determining basic questions about writing poetry, preparing a poetry writing project plan, preparing a poetry writing project schedule, implementing and monitoring a poetry writing project, assessing project results, and evaluating. The LKPD has been tested for suitability by material language experts with an 87% score in the